Esofagoplastia com retalho de pericárdio em gatos - Cunha, Olicies da (2001)
The efficiency of pediculated autogenous pericardial graft was tested as an alternative to repair esophageal thoracic defects in healthy domestic cats (n=12). Six of them were evaluated until 15 days and the another six until 30 days after surgery. They were submitted to thoracotomy in the fourth intercostal right space, and a pericardium flap was prepared through frenic nerve dissection, and blood vessels preservation, followed by production of the esophageal defect (0,5 x 1,0 cm) involving all layers. The flap was sutured on the defect with polyglactin 910, (n. 4.0 to 6.0), depending on animal size with horizontal mattress suture. The animals were clinically evaluated after surgery and, at the end of the period, 15th and 30th days, submitted to euthanasia and necropsied for esophagus macroscopic and microscopic evaluation, and stenosis measure. Confortable recovery, without clinical signs was observed in 9 animals, that showed good adaptation to feeding, without emesis, regurgitation, cough, dysphagia, and weight loss. Only one animal regurgitation was observed when solid food was offered, but it did not persist beyond three days. At macroscopic evaluation, a good esophageal repair was observed. In two animals, there were weight loss, besides dyspnea and hiporexia until euthanasia. In one of these animals, the signs were caused by piotorax. In the other, an esophagic fistula ocurred, caused by thoracic cavity contamination. The stenosis observed during euthanasia did not produce dysphagia. Histopathology showed esophageal epithelium regeneration over the pericardium without variation in 15 and in 30 days after surgery.